(untitled) (XXI Century. Spanish Literature and Culture, 2004)
The Spanish Transition unravels a literary atmosphere of disenchantment in which, through a reflective reading, we can see manifest with great care the nostalgia, the loss and the introspection. Be it ‘renovating’, ‘dreaming’ or ‘thoughtful’ nostalgia, all of them create a personal dissatisfaction that the author labels as a state of madness, not sanity, in which his study is focused.